Trichinella spiralis in a South American sea lion (Otaria flavescens) from Patagonia, Argentina - Pasqualetti, Mariana Ines; Fariña, Fernando Adrián; Krivokapich, Silvio Jesús; Gatti, G. M.; Daneri, Gustavo Adolfo; Varela, Esperanza Amalia; Lucero, Sergio; Ercole, Mariano Emmanuel; Bessi, Clara; Winter, Marina; Ribicich, Miriam Mabel (Parasitology Research)
Trichinella spp. from a sylvatic cycle has been found in several animal species such as pumas (Puma concolor), armadillos (Chaetophractus villosus), rats (Rattus norvegicus), and wild boars (Sus scrofa) in Argentina. Moreover, Trichinella infection has been detected in a wide range of marine mammals around the world, including polar bears (Ursus maritimus) and walruses (Odobenus rosmarus). Until the present time, Trichinella spp. infection has not been detected in marine mammals of South America. Samples from four South American sea lions (Otaria flavescens) found dead in Rio Negro, Argentina, were analyzed by artificial digestion, and in the case of one animal, Trichinella larvae were identified at the species level by nested multiplex PCR as Trichinella spiralis. This is the first report of a Trichinella species infecting marine mammals from South America. Fil: Pasqualetti, Mariana Ines. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Unidad Ejecutora de Investigaciones en Producción Animal. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias. Unidad Ejecutora de Investigaciones en Producción Animal; Argentina Fil: Fariña, Fernando Adrián. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Unidad Ejecutora de Investigaciones en Producción Animal. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias. Unidad Ejecutora de Investigaciones en Producción Animal; Argentina Fil: Krivokapich, Silvio Jesús. Dirección Nacional de Instituto de Investigación. Administración Nacional de Laboratorio e Instituto de Salud “Dr. C. G. Malbrán”; Argentina Fil: Gatti, G. M. Dirección Nacional de Instituto de Investigación. Administración Nacional de Laboratorio e Instituto de Salud “Dr. C. G. Malbrán”; Argentina Fil: ...